The THE ROLE OF AERVA JAVANICA (BURM.F.) JUSS. GROWING IN JAZAN, SAUDI ARABIA AS ANTIMICROBIAL AND COAGULATING FACTOR - Aldhebiani, Amal; Nagei, Taghreed; Alshaeri, Shareefa; Alsulaimany, Faten (European Journal of Applied Sciences, 2021)
In deserted conditions, plants suffer from shortage of water and minerals. Though, they try to adapt with harsh conditions by building an internal defense system via making different chemical compounds, especially secondary metabolites. These secondary metabolites have several medicinal effect. Saudi Arabia is considered as semi-arid region. Therefore, it has many plants with high adaptation level to survive in the exotic environment. South west of Saudi Arabia is the richest in plant biodiversity. One of the common plants that grows nearly everywhere in the country is Aerva javanica (Burm.f.) Juss. It is a widely distributed herbal plant and is called desert cotton (in Arabic Tarf). It has different human usage. Flowers sometimes are used as cotton filling for pillows. Moreover, it has different medicinal practices among indigenous people. One of its uses among local people is using flowers to stop the bleeding if wounds persists. Therefore, this research investigate the medicinal implication of A. javanica as antibacterial agent and as a blood-coagulating factor. Dichloromethane, methanol, ethanol and water extractions from different parts of the plant (stem, leaf and flower) were investigated. The antimicrobial activity of plant extracts were evaluated with microorganism by disc diffusion method on three different strains of bacteria (Escherichia coli, Staphylococcus aureus and Bacillus subtilis). Moreover, coagulating rate by manual method on blood samples from female rat was restrained. Escherichia coli growth was inhibited only by the dichloromethane extraction from the three parts of the plant. Staphylococcus aures growth was inhibited by the aqueous extraction of the three parts of the plant and the methanol extraction of the leaves. All the other extractions has no effect on the growth of Bacillus subtilis or the other bacteria. For the blood coagulating, all extracts were very effective on exceeding blood clotting time. The clotting time was less than the time of the control. The finding and results are discussed in detail.